Determination of Awareness of Piracy Level on Educational Institutions- A Questionnaire Based Study - Nazir, Shah; Hussain, Anwar; Shahzad, Sara; Ur Rehman, Hanif; Zada, Islam; Ahsan, Muhammad; Ahmad, Zohaib; Khan, Abdullah (EAI Endorsed Transactions on Energy Web, 2018)
Software piracy is globally a major issue of using software without proper permission as enforced by the software license and agreement. Currently, software industries and organizations face a huge loss of money due to software piracy. Most of the educational institutions/organizations have also been affected from software piracy. To facilitate educational institutions regarding software piracy, it would be ideal to have a detailed study of the awareness of piracy level in education institutions for future development and to help academia to get rid of problems occur from pirated software. The present research aims to study and determine the awareness of piracy level in educational institutions. This study will eventually help academia in determination of level of piracy and awareness of pirated software.